Handbook on Intangible Cultural Practices as Global Strategies for the Future Twenty Years of the UNESCO Convention on Safeguarding Intangible Cultural Heritage - Wulf, Christoph (Heritage Studies, 2025)
XI, 579 p. 25 illus.